Evaluation of long-lasting insecticidal net distribution through schools in Southern Tanzania. Issue 2 (17th December 2021) - Stuck, Logan; Chacky, Frank; Festo, Charles; Lutambi, Angelina; Abdul, Ramadhani; Greer, George; Mandike, Renata; Nathan, Rose; Elisaria, Ester; Yukich, Joshua
Abstract: Universal coverage with effective vector control remains the mainstay of malaria vector control in sub-Saharan Africa. Tanzania has utilized a number of mechanisms for the maintenance of long-lasting insecticidal net (LLIN) coverage over time. Schools have been identified as one potential channel for continuous distribution of LLIN. This research aims to evaluate an annual school-based LLIN distribution programme in Tanzania that began in 2013, called the School Net Programme (SNP). Following each of the first four rounds of SNP distribution, a household survey was conducted in intervention and comparison districts in Southern and Lake zones of Tanzania ( N  = 5083 households). Measures of ownership, access and use were compared between intervention and comparison districts. Determinants of reach were assessed in intervention districts. Population access to an LLIN increased from 63.1% (95% CI: 58.8, 67.5) to 76.5% (95% CI: 72.9, 80.0) in the intervention districts between the first and last surveys. Access also rose in the comparison districts from 51.4% (95% CI: 46.9, 55.9) to 79.8% (95% CI: 77.3, 82.0) following mass distribution and implementation of school-based distribution during the study period. LLIN use increased in intervention districts from 44.9% (95% CI: 40.5, 49.3) to 65.6% (95% CI: 59.4, 71.8) and from 57.2% (95% CI: 49.7, 64.7) to 77.4% (95% CI: 69.3, 85.5) specifically amongst primary school-aged children. Households reached by the SNP were wealthier households with children enrolled in school. The SNP in Tanzania was able to maintain population level LLIN ownership, use and access in the absence of mass distribution. The SNP successfully reached households that housed school-aged children. Alternative delivery strategies may need to be considered to reach households without children enrolled in schools that experienced fewer benefits from the programme.